Ageing and muscular dystrophy differentially affect murine pharyngeal muscles in a region‐dependent manner. (3rd November 2014) - Randolph, Matthew E.; Luo, Qingwei; Ho, Justin; Vest, Katherine E.; Sokoloff, Alan J.; Pavlath, Grace K.
Key points Millions of elderly individuals have dysphagia, a debilitating and life‐threatening condition in which the ability to swallow is impaired. Several muscles surround the three regions of the pharynx, which are essential for proper swallowing, yet the effects of ageing and disease on these muscles are not well understood. We demonstrate that the fibre size of murine pharyngeal muscles is differentially affected by ageing and muscular dystrophy depending on their location within the pharynx. Using a mouse model of an age‐associated dysphagic disease (oculopharyngeal muscular dystrophy), we show that overexpression of wild‐type polyadenylate binding nuclear protein 1 in muscle tissue prevents age‐related dysphagia and age‐related muscle atrophy of laryngopharyngeal muscles. These results demonstrate that mice are an excellent model for studying mechanisms of ageing and disease on pharyngeal muscle physiology, and such studies could lead to new therapies for individuals with dysphagia. Abstract The inability to swallow, or dysphagia, is a debilitating and life‐threatening condition that arises with ageing or disease. Dysphagia results from neurological or muscular impairment of one or more pharyngeal muscles, which function together to ensure proper swallowing and prevent the aspiration of food or liquid into the lungs. Little is known about the effects of age or disease on pharyngeal muscles as a group. Here we show ageing affected pharyngeal muscle growth and atrophy in wild‐type mice depending on the particular muscle analysed. Furthermore, wild‐type mice also developed dysphagia with ageing. Additionally, we studied pharyngeal muscles in a mouse model for oculopharyngeal muscular dystrophy, a dysphagic disease caused by a polyalanine expansion in the RNA binding protein, PABPN1. We examined pharyngeal muscles of mice overexpressing either wild‐type A10 or mutant A17 PABPN1. Overexpression of mutant A17 PABPN1 differentially affected growth of the palatopharyngeus muscle dependent on its location within the pharynx. Interestingly, overexpression of wild‐type A10 PABPN1 was protective against age‐related muscle atrophy in the laryngopharynx and prevented the development of age‐related dysphagia. These results demonstrate that pharyngeal muscles are differentially affected by both ageing and muscular dystrophy in a region‐dependent manner. These studies lay important groundwork for understanding the molecular and cellular mechanisms that regulate pharyngeal muscle growth and atrophy, which may lead to novel therapies for individuals with dysphagia.